The role of public transport in the achievement of urban sustainable mobility in mid-sized cities - Ribeiro, Paulo (2010)
Mid-sized cities or villages often have important issues associated with the relation between demand and supply of transport, due to its own spatial dimension and also due to the territory sprawl derived from years of deficient land use planning. Traditionally, public transport was mainly designed to cover and serve the entire municipality, giving a rural character to this service. Presently, some of these cities are sufficiently large to support the adoption of an urban public transport. The main question is how to create a public transport service in mid-sized cities integrated with the existing transport and parking system, so that more sustainable patterns of mobility can be achieved. For this purpose, a case study will be presented regarding the creation and planning of an urban public transport service for the city of Barcelos, located in Northern Portugal.